2018
DOI: 10.1038/s41377-018-0097-7
|View full text |Cite
|
Sign up to set email alerts
|

A stoichiometric terbium-europium dyad molecular thermometer: energy transfer properties

Abstract: The optical thermometer has shown great promise for use in the fields of aeronautical engineering, environmental monitoring and medical diagnosis. Self-referencing lanthanide thermo-probes distinguish themselves because of their accuracy, calibration, photostability, and temporal dimension of signal. However, the use of conventional lanthanide-doped materials is limited by their poor reproducibility, random distance between energy transfer pairs and interference by energy migration, thereby restricting their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(76 citation statements)
references
References 45 publications
2
73
0
1
Order By: Relevance
“…The plot of the relative sensitivity against temperature in Figure e reveals maximum relative sensitivity of 16.14% K −1 at 359 K. Notably, a high S r of 9.01% K −1 at 353 K was also attained over the physiological temperature range (293–353 K), which outperforms existing luminescence thermometers in this temperature range (Table S2, Supporting Information) …”
mentioning
confidence: 86%
“…The plot of the relative sensitivity against temperature in Figure e reveals maximum relative sensitivity of 16.14% K −1 at 359 K. Notably, a high S r of 9.01% K −1 at 353 K was also attained over the physiological temperature range (293–353 K), which outperforms existing luminescence thermometers in this temperature range (Table S2, Supporting Information) …”
mentioning
confidence: 86%
“…For example, Tb* to Eu energy transfer occurs in the solid state 55,56 and in solution, and can be controlled in well-designed series of heterodinuclear complexes. 57 In a dinuclear system with the Tb and Eu ions believed to be separated by 10.6 Å, it has been found that energy transfer from Tb 5 D 4 to Eu 7 F 1 was most efficient and was thermally activated. Earlier work had shown that if the transitions are not exactly at resonance, for a Förster transfer mechanism the energy difference must be conserved by phonons.…”
Section: Energy Transfer Quenching K Et Involving the Metal Excited Statementioning
confidence: 99%
“…The relative proximity of the excited state energies of Eu 3+ (~17,240 cm er1 ) and Tb 3+ (~20,400 cm −1 ) and the relatively small metal-to-metal distances in most common structures [ 51 ] cannot only provide two independent luminescence processes for each of the ions but also allow the transfer of excitation energy from Tb 3+ ions to Eu 3+ . The thermal dependence of the efficiency of such transfer mainly determines the working mechanism of “luminescent thermometers” [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, quite often, the luminescence excitation spectra of Eu 3+ contain peaks corresponding to the excitation of Tb 3+ ions [ 10 , 51 ]. Third, introducing Eu 3+ ions reduces the lifetimes of the excited state of terbium(III) ions significantly [ 52 ]. Finally, in a number of cases, decay curves of Eu 3+ are not described satisfactorily by usual single- or biexponential models but contain the initial growth period [ 10 ].…”
Section: Introductionmentioning
confidence: 99%